2016
DOI: 10.1002/zaac.201600281
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Open-Framework of a Bipyridinium-Carboxylate Based Copper Complex with High and Reversible Water Uptake

Abstract: The rigid zwitterionic ligand 1,1′‐bis(4‐carboxylatphenyl)‐(4,4′‐bipyridinium) (pc1) and copper(II) ions give rise to a linear complex [Cu(pc1)2(H2O)4]2+, which self assembles in a pseudo tetragonal supramolecular arrangement leading to the supramolecular open‐framework [Cu(pc1)2(H2O)4](Cl)2·8H2O exhibiting an open structure including water molecules and chlorides in pores. The dehydration of this material occurs at relatively low temperature (70 °C) and results in structure modification accompanied by shrinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Another possibility of constructing these 2-D soft porous crystals is the use of tectons which are able to self-assemble with weak interactions and form porous supramolecular networks (PSN). One of the compounds recently published in this class is the [Cu­(pc1) 2 (H 2 O) 4 ]­(Cl) 2 ­·8H 2 O where the [Cu­(pc1) 2 (H 2 O) 4 ] 2+ complexes (pc1 = 1,1-bis­(4-carboxylatphenyl)-(4,4-bipyridinium)) self-assemble through hydrogen bonds involving the free carboxylate groups and the water molecules linked to copper ions leading to an open 2-D supramolecular network. In this regard, the self-assembly of cationic and anionic complexes capable of being involved in well-identified intermolecular interactions such as hydrogen bonds could be made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility of constructing these 2-D soft porous crystals is the use of tectons which are able to self-assemble with weak interactions and form porous supramolecular networks (PSN). One of the compounds recently published in this class is the [Cu­(pc1) 2 (H 2 O) 4 ]­(Cl) 2 ­·8H 2 O where the [Cu­(pc1) 2 (H 2 O) 4 ] 2+ complexes (pc1 = 1,1-bis­(4-carboxylatphenyl)-(4,4-bipyridinium)) self-assemble through hydrogen bonds involving the free carboxylate groups and the water molecules linked to copper ions leading to an open 2-D supramolecular network. In this regard, the self-assembly of cationic and anionic complexes capable of being involved in well-identified intermolecular interactions such as hydrogen bonds could be made.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics have also been observed in a family of compounds named "elastic layer-structured metal− organic frameworks (ELMs)". 23 24 where the [Cu(pc1) 2 (H 2 O) 4 ] 2+ complexes (pc1 = 1,1-bis(4-carboxylatphenyl)-(4,4-bipyridinium)) self-assemble through hydrogen bonds involving the free carboxylate groups and the water molecules linked to copper ions leading to an open 2-D supramolecular network. In this regard, the self-assembly of cationic and anionic complexes capable of being involved in well-identified intermolecular interactions such as hydrogen bonds could be made.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the hydrogen-bond networks can provide hydrogen-bond sites that interact weakly with volatile carbonyl compounds. The characteristics of metal-complex-based hydrogen-bond networks have been investigated for more than two decades (for selected reviews, see refs ; for recent examples, see refs ); nevertheless, the adsorption/desorption properties of volatile carbonyl compounds in such networks have not been explored, except in the case of acetone. Takamizawa et al have measured the adsorption isotherm of acetone in a hydrogen-bond network derived from [Co­(ethylenediamine) 3 ]­Cl 3 . The Beatty group has investigated the desorption of co-crystallized acetone from the crystals of [M­(2,4-pyridine dicarboxylate) 2 ] 2– , where M was Cu or Zn. , Castillo and co-workers have confirmed that a [Cu 2 (μ-adenine) 4 Cl 2 ]­Cl 2 -based hydrogen-bond network can adsorb acetone .…”
Section: Introductionmentioning
confidence: 99%